Do-re-mi Self Motivation in Breast Cancer Patients: A Qualitative Study - Padoli, Padoli; Hasanah, Nur; Adinata, Ach Arfan (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: In Indonesia, breast cancer is the most prevalent type of cancer and a leading cause of cancer-related deaths. It is important to motivate the patients to fight the disease and to adapt to the illness and the treatments. This active sense of motivation helps them to feel secure and keeps the thoughts of death at a safe distance. AIM: The aim of this study was to explore the emotions that motivate breast cancer patients. The study was qualitative in nature. METHODS: This study involved 16 participants who were selected through purposive sampling at the Shelter House East Java Branch in Surabaya, Indonesia. The researchers used in-depth interviews to collect the data and the Colaizzi method was employed for the data analysis. RESULTS: Seven themes emerged from the data: Drive/Self-Motivation, respect yourself, precious self, facts of success, solutions taken to overcome problems, next strategy, and supportive situation. CONCLUSION: Positive attitudes and strategies that help breast cancer patients cope with their illness, include self-motivation, self-respect and valuing oneself, focusing on personal achievements, and seeking support, abbreviated as Do-re-mi. These findings could be used as self-talk content to develop self-affirmation strategies for breast cancer patients to help them accept their situation and reduce stress. The purpose of his study aims to explore self-motivation response of breast cancer clients. The type of research used in this study is a qualitative description.